2016
DOI: 10.1097/md.0000000000005094
|View full text |Cite
|
Sign up to set email alerts
|

CD4/CD8 ratio and CD8 counts predict CD4 response in HIV-1-infected drug naive and in patients on cART

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
(39 reference statements)
3
17
0
2
Order By: Relevance
“…Study SHSC (2016) showed that the CD4/CD8 ratio was an important time-dependent prognostic factor, for the treatment of HIV naive patients and patients treated with cART. Data from this study confirmed the association between HIV/AIDS disease progression and the time needed for normalization of the CD4/CD8 ratio (22,23).…”
Section: Discussionsupporting
confidence: 76%
“…Study SHSC (2016) showed that the CD4/CD8 ratio was an important time-dependent prognostic factor, for the treatment of HIV naive patients and patients treated with cART. Data from this study confirmed the association between HIV/AIDS disease progression and the time needed for normalization of the CD4/CD8 ratio (22,23).…”
Section: Discussionsupporting
confidence: 76%
“…In other predictive research [7], the use of absolute leukocyte count has been proposed as a surrogate to establish the quantity of CD4 + cells, predicting counts < 200 cells/µL 3 with sensitivity and speci city values between 20.2% and 61%. Other predictive approximations have been conducted achieving more precise values [6,15,16] considering other markers such as the CD4+/CD8 + ratio [17] or the CD4 + percentage [18]. More recently, data mining algorithms such as Random Forest [19] have been developed to predict values of CD4 + < 100 cells/µL 3 , obtaining a precision close to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The mathematical patterns found between leukocytes and CD4 + cell counts as well as the high probability and accurate values for each of the ranges studied, since two were of 1 and the remaining above 0.94, suggesting that this phenomenon is highly deterministic. Different studies have been developed to substitute the value of CD4 + cell through the absolute lymphocyte count (4-7, 15-17) as well as to predict the value of these cells through other variables as viral load (10), data mining (18) or CD4 + /CD8 + ratio (19). However, these proposals do not achieve adequate performances neither possess reproducibility among the different studies conducted, since they present variations according to age and populational groups studied.…”
Section: Discussionmentioning
confidence: 99%